IMPLEMENTING TASK BASED LANGUAGE TEACHING (TBLT) INSTRUCTION TO IMPROVE STUDENTS’ SPEAKING PARTICIPATION IN ISLAMIC BOARDING SCHOOL OF MAULANA MALIK IBRAHIM, STATE ISLAMIC UNIVERSITY OF MALANG - Khusnul Khotimah (Universitas Islam Lamongan, 2018)
English speaking ability has long been considered as one of the most crucial materials for a bilingual program in Islamic Boarding School of Maulana Malik Ibrahim, State Islamic University of Malang. Since students of that Islamic Boarding School are demanded to be able to communicate in English, motivation and training to comprehend in mastering it are needed. However, some students consider speaking as the most difficult one since it needs great courage as well as preparation to produce the language. Either beginner or advanced students participate passively when joining Sobaghul Lughoh program. The researcher is interested conducting a research for Advance class because they are considered having good capability either verbal or oral in English but they seem passive participating in the class. The researcher uses Classroom Action Research (CAR) to analyze and solve the problems faced by the Advance class. Furthermore, the researcher concerns on their speaking participation rather than other skills because speaking is productive skill which can be directly and empirically observed. The result is the students enthused joining the program and participated much in doing the task. Finally, Implementing Task Based Language Teaching (TBLT) instruction in Sobaghul Lughoh Program has showed conclusion that this method is appropriate to be applied. This strategy is able to improve students’ speaking participation in class. Their participation in completing tasks, discussion and conversation shows that they are active and enthusiasm following the program. Key Words: TBLT, Speaking, Sobaghul Lughoh Program